Low-cost carbon-based counter electrodes for dye sensitized solar cells. (29th July 2015) - Barberio, M; Imbrogno, A; Grosso, D R; Bonanno, A; Xu, F
Abstract: In this work, we present the realization of four carbon-based counter electrodes for dye-sensitized solar cells. The photovoltaic behaviours of counter electrodes realized with graphene, multiwalled carbon nanotubes, and nanocomposites of multiwalled carbon nanotubes and metal nanoparticles are compared with those of classical electrodes (amorphous carbon and platinum). Our results show an increase of about 50% in PCE for graphene and Ag/carbon nanotube electrodes with respect to amorphous carbon and of 25% in comparison to platinum. An improvement in cell stability is also observed; in fact, the PCE of all carbon-based cells assumes a constant value during a period of one month while that with the Pt electrode decreases by 50% in one week.